Comparative genomic analysis between Corynebacterium pseudotuberculosis strains isolated from buffalo. - Marcus Vinicius Canário Viana; Henrique Figueiredo; Rommel Ramos; Luis Carlos Guimarães; Felipe Luiz Pereira; Fernanda Alves Dorella; Salah Abdel Karim Selim; Mohammad Salaheldean; Artur Silva; Alice R Wattam; Vasco Azevedo (PLoS ONE, 2017)
Corynebacterium pseudotuberculosis is a Gram-positive, pleomorphic, facultative intracellular pathogen that causes Oedematous Skin Disease (OSD) in buffalo. To better understand the pathogenic mechanisms of OSD, we performed a comparative genomic analysis of 11 strains of C. pseudotuberculosis isolated from different buffalo found to be infected in Egypt during an outbreak that occurred in 2008. Sixteen previously described pathogenicity islands (PiCp) were present in all of the new buffalo strains, but one of them, PiCp12, had an insertion that contained both a corynephage and a diphtheria toxin gene, both of which may play a role in the adaptation of C. pseudotuberculosis to this new host. Synteny analysis showed variations in the site of insertion of the corynephage during the same outbreak. A gene functional comparison showed the presence of a nitrate reductase operon that included genes involved in molybdenum cofactor biosynthesis, which is necessary for a positive nitrate reductase phenotype and is a possible adaptation for intracellular survival. Genomes from the buffalo strains also had fusions in minor pilin genes in the spaA and spaD gene cluster (spaCX and spaYEF), which could suggest either an adaptation to this particular host, or mutation events in the immediate ancestor before this particular epidemic. A phylogenomic analysis confirmed a clear separation between the Ovis and Equi biovars, but also showed what appears to be a clustering by host species within the Equi strains.